Ab‐Initio Molecular Dynamics Simulation of the Electrolysis of Waste Water. Issue 14 (15th April 2019) - Frank, Irmgard
Abstract: Electrolysis is potentially a valuable method for cleansing waste water. Chemically the process is ultra‐fast and highly complex. In the present study the products formed at the cathode and anode are investigated using Car‐Parrinello molecular dynamics. To make a start into this vast field, relatively simple mixtures are investigated. The simulations of the anodic process are performed for urea and uric acid in water containing discharged hydroxide. The cathodic process is simulated for urea and uric acid in water with discharged ammonium ions. While at the cathode mainly molecular hydrogen is developed, the chemistry at the anode is rather complex. We observe unstable intermediates which are probably toxic. Abstract : Wild mixture: The electrolysis of waste water is simulated using Car‐Parrinello molecular dynamics simulations. The quantum chemical description of the electronic cloud allows the simulation of arbitrary reaction types. For the nuclear motion a classical description is chosen. In the simulations short‐lived intermediates are observed which were not discussed before.